BACTERIAL CELLULOSE FROM RICE WASTE WATER AND ITS COMPOSITE WHICH ARE DEPOSITED NANOPARTICLE AS AN ANTIMICROBIAL MATERIAL - Eli Rohaeti; Endang W Laksono; Anna Rakhmawati (UNIVERSITAS SEBELAS MARET (UNS), 2016)
Bacterial cellulose (C) and its composites were synthesized from rice waste water with addition of glycerol (G) and chitosan (Ch).Antibacterial activity of the C, the bacterial cellulose-chitosan composite (CCh), and the bacterial cellulose – glycerol - chitosan composite (CGCh) which were deposited silver nanoparticles against S. aureus, E. coli, and yeast C. albicans has been conducted. Silver nanoparticles was prepared by chemical reduction of a silver nitrate solution, a trisodium citrate as a reductor, and a PVA as a stabilizer. The UV-Vis spectroscopy is used to determine the formation of silver nanoparticles. The characterization was conducted on the bacterial celluloses and those composites including the functional groups by the FTIR, the mechanical properties by Tensile Tester, photos surfaces by SEM, and the test of the antibacterial activity against S. aureus, E. coli, and C. albicans by diffusion method. The silver nanoparticle characterization indicates that the silver nanoparticles are formed at a wavelength of 418.80 nm. The antibacterial test showed an inhibitory effect of the C, the CCh, and the CGCh which are deposited the silver nanoparticles against of S. aureus, E. coli, and C.albicans. The CGChs which are deposited silver nanoparticles has the highest antimicrobial activity against the Staphylococcus aureus ATCC 25923. The CGs which are deposited silver nanoparticles provide the highest antimicrobial activity against the E. coli ATCC 25922 and the yeast Candida albicans ATCC 10231.